A method for characterizing the deformation localization in granular materials using the relative particle motion. (April 2023) - Lu, Dechun; Dong, Hongyu; Lin, Qingtao; Guo, Caixia; Gao, Zhiwei; Du, Xiuli
Abstract: The failure location identification of granular materials can be solved by capturing the deformation localization. Considering the relative translation and rotation among particles, a new concept named the relative particle motion (RPM) is proposed to describe the deformation localization of the granular materials. An approach is developed to realize the selection of particles that are used to calculate RPM. The number of particles involved in RPM calculation is controlled by two key parameters, i.e., grid spacing ( U ) and domain radius ( R ). Combining the proposed concept and the selection approach of particles, the method that can capture the region of the deformation localization in the granular material is established and implemented in PFC2D.The simulation of a uniaxial compression test is conducted to analyze the effect of parameters U and R on the calculation results of the RPM field, and a reasonable range of U and R is given. Three typical conditions, including the biaxial compression, trapdoor, and particle flow tests, are taken as examples to validate the proposed method under different loading conditions. Regions of the deformation localization characterized by RPM have a good agreement with the shear band presented in the published literature.